KELEMBAGAAN OTONOMI KHUSUS (OTSUS) DALAM MEMPERTAHANKAN NILAI-NILAI KEBUDAYAAN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Annafie, Khotman; Nurmandi, Achmad (Universitas Muhammadiyah Yogyakarta, 2016)
When the Law No. 32 of 2004 on Regional Government was passed, which was originally centralized to decentralized, then wujudkannya regional autonomy. In addition to the inception of the autonomous regional government also established a special department to conduct government functions that are specific, D.I Yogyakarta one with Act No. 13 of 2012 on Privileges D.I Yogyakarta. Special Region of Yogyakarta has authority to maintain cultural values, the need for institutions that are able to maintain the cultural wisdom. This type of research is descriptive quantitative research. The type of data that are used are primary data and secondary data, with interview techniques and documentation. The analysis unit is composed of theÂ Department of Culture DIY, DIY DPRD Commission D and the palace DIY. Interactive analysis techniques using a model consisting of three things: data reduction, data presentation and conclusion. Based on the results of the study concluded that the regulatory pillar in this study was measured by an indicator of rules or laws relating to cultural values, sanctions and monitoring. Regulative as factors supporting the implementation of cultural values able to push all the elements in the institution and community groups in order to apply the values of the culture in daily life hari.Pilar normative in this study was measured by an evaluation and the obligations and responsibilities in the institutional Autonomy jawab.Evaluasi field Culture has been done by issuing a regulation on protecting the culture in DIY. Keywords: Privileged DIY, Special Autonomy and Institutions